Sacrococcygeal dermal sinus associated with occult spinal dysraphim. Report of an atypical case and literature review. - Pirozzi Chiusa, Christian Gabriel; Cardona, Carlo; Barbone, Félix (Revista Argentina de Neurocirugía, 2022)
The sacrococcygeal dermal sinus is a frequent entity in newborns, whose incidence is estimated between 2 to 4%. It consists of a depression at the upper end of the gluteal fold, which may extend to the coccyx. Its etiology is controversial and the form of presentation is varied, from asymptomatic dimples to painful abscesses that drain to the skin surface. It must be differentiated from the spinal dermal sinus, a dysraphism that is often accompanied by other congenital anomalies. In contrast, the pilonidal sinus is rarely associated with spinal dysraphisms. We present the case of a 21-year-old male patient with hypertrichosis and sacral subcutaneous tumor, who consulted for pain and purulent discharge of two weeks of evolution. On physical examination, we observed two skin holes on the upper edge of the intergluteal fold. Neuroimaging studies showed dysraphism of the sacral segments, tethered cord, and sacrococcygeal dermal sinus. The sacrococcygeal pilonidal sinus has a multifactorial etiology, which can unusually be associated with spina bifida occulta and congenital skin lesions. Early identification of spinal dysraphism is essential for proper neurosurgical management and the prevention of neurological sequelae.